2016
DOI: 10.1007/978-3-319-25979-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lipids in Photosynthesis

Abstract: Thylakoid membranes in cyanobacterial cells and chloroplasts of algae and higher plants are the sites of oxygenic photosynthesis. The lipid composition of the thylakoid membrane is unique and highly conserved among oxygenic photosynthetic organisms. Major lipids in thylakoid membranes are glycolipids, monogalactosyldiacylglycerol, digalactosyldiacylglycerol and sulfoquinovosyldiacylglycerol, and the phospholipid, phosphatidylglycerol. The identification of almost all genes involved in the biosynthesis of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 117 publications
2
57
0
Order By: Relevance
“…Whereas the increase in glycolipid (MGDG, DGDG and SQDG) content was gradual, that in PG content was rapid particularly between 9 and 24 h after N addition. This observation is consistent with the special importance of PG for the structure and function of photosystems (Kobayashi et al, 2016). Unlike glycolipids that are mostly used to form the lipid bilayer of thylakoid membranes, a large proportion of PG is allocated to photosystem complexes as a structural component (Kobayashi et al, 2017).…”
Section: Reconstruction Of Thylakoid Membrane Systems After N Additionsupporting
confidence: 84%
See 1 more Smart Citation
“…Whereas the increase in glycolipid (MGDG, DGDG and SQDG) content was gradual, that in PG content was rapid particularly between 9 and 24 h after N addition. This observation is consistent with the special importance of PG for the structure and function of photosystems (Kobayashi et al, 2016). Unlike glycolipids that are mostly used to form the lipid bilayer of thylakoid membranes, a large proportion of PG is allocated to photosystem complexes as a structural component (Kobayashi et al, 2017).…”
Section: Reconstruction Of Thylakoid Membrane Systems After N Additionsupporting
confidence: 84%
“…These glycerolipids form a lipid bilayer of the thylakoid membrane, which avoids free diffusion of ions and allows for generating an electrochemical potential difference across the membrane for ATP synthesis. Besides providing a matrix embedded with protein-pigment complexes and ATP synthase, glycerolipids in thylakoids play essential roles in photosynthesis as structural and functional components of PSII, cytochrome b 6 f and PSI (Kobayashi et al, 2016). Thus, biogenesis of the thylakoid membrane with the functional photosynthetic machinery needs coordinated synthesis and assembly of proteins, cofactors including Chls, and glycerolipids, as represented by essential roles of galactolipids in the thylakoid membrane organization during chloroplast development in Arabidopsis thaliana (Fujii et al, 2019b).…”
mentioning
confidence: 99%
“…The diploid E. huxleyi stage also had a slightly higher concentration of polar lipids under nutrient‐replete conditions, especially concerning the fatty acids C 18:1n9cis , C 18:2n6cis , C 18:4n3 , C 22:0 , and C 22:6n3 , indicating differences in membrane composition. The higher abundance of polyunsaturated fatty acids could reflect differences in thylakoid membrane composition (Fulton et al ), which has been shown for haploid and diploid E. huxleyi strains before (Bell and Pond ; Fiorini et al ; Hunter et al ), and could influence photosynthetic efficiency (Kobayashi et al ). As mentioned above, differences in polar lipid composition could be attributed to diploid‐specific compartments such as vesicles for calcium carbonate pre‐concentration (Sviben et al ), and coccolith vesicle structures (Sawada and Shiraiwa ; Eltgroth et al ), or viral susceptibility (Hunter et al ).…”
Section: Discussionmentioning
confidence: 95%
“…Mutants impaired in lipid metabolism in cyanobacteria or chloroplasts of plants have thus far been examined as to their impact on the structural and functional integrity of the oxygenic photosynthetic apparatus, whereby, the correlation of lipids, i.e., the final products of the lipid synthesis pathways, to photosynthesis has been discussed (reviewed in, e.g., [31]). Such studies include those concerning SQDG- and/or PG-deficient mutants of Synechocystis or C .…”
Section: Discussionmentioning
confidence: 99%